An Analytical Method for Determining the Stress–Strain State of a Subgrade with Combined Reinforcement - Ahmad Alkhdour; Oleksii Tiutkin; Szabolcs Fischer; Dmytro Kurhan (Infrastructures)
This article presents the fundamentals of an analytical method for determining the stress–strain state of a railway subgrade reinforced with geosynthetic material. The reinforcement described is a combined system where the geosynthetic material forms an open shell containing a layer of compacted crushed stone. The overall stress–strain state is proposed to be viewed as a superposition of two states of the subgrade. The stresses and displacements in the first state refer to the unreinforced subgrade (matrix), while the stress–strain state of the reinforcement element is determined using analytical constructs from composite theory. The dependencies of the overall stress–strain state are applied in a numerical analysis, which confirms the positive effect of reduced subgrade deformations. A small-scale experimental model further validates the accuracy of the analytical approach.